Analisis Perbandingan Kinerja Keuangan Perusahaan Food & Beverage Sebelum dan Sesudah Diwajibkannya Sertifikat Halal di Indonesia - Cholis, Muhammad; Darmanto (Jurnal Ilmiah Aset, 2025)
The Indonesian government, through Law No. 33 of 2014, committed to requiring companies operating in the food and beverage industry to pass Halal certification. This was followed up by Government Regulation No. 39 of 2021, which requires all companies, from micro, medium, and large enterprises, to pass and obtain Halal certification for all their products by 2024. Therefore, in this study, researchers took samples using purposive sampling from the food and beverage industry group listed on the Indonesia Stock Exchange for the period 2023 and 2024. The aim was to determine the extent to which the required Halal certification can boost company performance and profitability. Therefore, this study compared net sales and profitability ratio variables before and after the mandatory Halal certification. The results of the study indicate that company performance, as measured by net sales, significantly differed before and after the Indonesian government mandated halal certification. This performance improved after the mandatory halal certification period. Meanwhile, profitability ratios did not significantly differ between the periods before and after the mandatory halal certification period. A decrease in profitability was also observed after the mandatory halal certification period. This is due to other factors influencing the profitability ratio, which can be identified and further research can be conducted.